REDEFINING WORK-LIFE DYNAMICS IN HEALTHCARE: THE EMERGENCE OF WORK-LIFE FUSION IN VIKSIT BHARAT 2047 - Ms. Shweta Soni; Dr. Vibhuti Pareek; Dr. Kunal Rawal (Genetics and Molecular Research, 2026)
The evolving healthcare landscape, shaped by digital transformation and socio-economic change, necessitates a redefinition of traditional work–life paradigms. This study explores the emergence of Work–Life Fusion (WLF) as an integrative approach within the framework of Viksit Bharat 2047. Adopting a qualitative, exploratory, and descriptive design, the research synthesizes secondary data from policy documents, academic literature, and global reports to examine the conceptual foundations, drivers, and implications of WLF in healthcare. The study highlights how technological advancements, shifting workforce expectations, and post-pandemic work models have blurred boundaries between personal and professional domains. A conceptual framework linking Work-Life Integration Capability, Human Development Infrastructure, and Socioeconomic Transformation Outcomes is proposed to explain how WLF contributes to productivity, inclusivity, and well-being. The findings indicate that WLF can enhance workforce resilience, promote gender participation, support regional development, and improve mental health outcomes. However, challenges such as digital fatigue, infrastructural disparities, and cultural resistance remain significant. The study concludes that integrating WLF into policy and organizational strategies is essential for fostering a human-centric, sustainable, and future-ready healthcare system aligned with national development goals.